Representations of Slave Women in Discourses on Slavery and Abolition, 1780-1838 - Altink, Henrice (Routledge Studies in Slave and Post-Slave Societies and Cultures, 2007)
This book analyzes textual representations of Jamaican slave women in three contexts--motherhood, intimate relationships, and work--in both pro- and antislavery writings. Altink examines how British abolitionists and pro-slavery activists represented the slave women to their audiences and explains not only the purposes that these representations served, but also their effects on slave women's lives.